2017
DOI: 10.1186/s40798-017-0086-z
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Individual Exercise Training Components to Clinical Outcomes in Randomised Controlled Trials of Cardiac Rehabilitation: A Systematic Review and Meta-regression

Abstract: BackgroundWhile the clinical benefits of exercise-based cardiac rehabilitation are well established, there is extensive variation in the interventions used within these trials. It is unknown whether variations in individual components of these exercise interventions provide different relative contributions to overall clinical outcomes. This study aims to systematically examine the relationship between individual components of the exercise intervention in cardiac rehabilitation (such as intensity and frequency)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 127 publications
0
47
0
13
Order By: Relevance
“…Abell et al recently reviewed the contribution of individual exercise training components to clinical outcomes in randomized trials of cardiac rehabilitation and identified adherence to exercise prescription, not exercise intensity, session duration, or frequency, as a predictor of mortality 119. This result was also found in a long‐term analysis of 435 cardiac rehabilitation participants in Leeds, UK 122.…”
Section: Exercise Prescriptionmentioning
confidence: 84%
See 3 more Smart Citations
“…Abell et al recently reviewed the contribution of individual exercise training components to clinical outcomes in randomized trials of cardiac rehabilitation and identified adherence to exercise prescription, not exercise intensity, session duration, or frequency, as a predictor of mortality 119. This result was also found in a long‐term analysis of 435 cardiac rehabilitation participants in Leeds, UK 122.…”
Section: Exercise Prescriptionmentioning
confidence: 84%
“…In patients with heart failure, serious adverse events were numerically higher with HIT than with MCT. This finding and the association of myocardial infarction, need for coronary intervention, and mortality in patients with CAD with exercise session duration or intensity, even though these findings are controversial, should receive attention in future trials 17, 18, 77, 119…”
Section: Exercise Prescriptionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recent research has revealed that post-MI exercise training is associated with reductions in mortality and reinfarction; therefore, exercise training rather than the traditional instructions to avoid physical activity should be a part of cardiac rehabilitation programmes for MI. 39,40 However, the timing of the exercise training after MI has not yet been optimized. It has been revealed that moderate exercise beginning 5-7 days after MI is safe.…”
Section: Discussionmentioning
confidence: 99%